The stepsisters - Mallery, Susan (Mira, 2021)
Brought back together when Cassidy, the little sister they have in common, suddenly needs them both, Daisy and Sage must cast aside their hatred for each other to care for Cassidy and are caught off guard when long-buried secrets lead to forgiveness and a powerful friendship.